From prevention to diagnosis and treatment: Biomedical applications of metal nanoparticle-hydrogel composites. (1st March 2021) - Clasky, Aaron J.; Watchorn, Jeffrey D.; Chen, Paul Z.; Gu, Frank X.
Abstract: Recent advances in biomaterials integrate metal nanoparticles with hydrogels to generate composite materials that exhibit new or improved properties. By precisely controlling the composition, arrangement and interactions of their constituents, these hybrid materials facilitate biomedical applications through myriad approaches. In this work we seek to highlight three popular frameworks for designing metal nanoparticle-hydrogel hybrid materials for biomedical applications. In the first approach, the properties of metal nanoparticles are incorporated into a hydrogel matrix such that the composite is selectively responsive to stimuli such as light and magnetic flux, enabling precisely activated therapeutics and self-healing biomaterials. The second approach mediates the dynamic reorganization of metal nanoparticles based on environment-directed changes in hydrogel structure, leading to chemosensing, microbial and viral detection, and drug-delivery capabilities. In the third approach, the hydrogel matrix spatially arranges metal nanoparticles to produce metamaterials or passively enhance nanoparticle properties to generate improved substrates for biomedical applications including tissue engineering and wound healing. This article reviews the construction, properties and biomedical applications of metal nanoparticle-hydrogel composites, with a focus on how they help to prevent, diagnose and treat diseases. Discussion includes how the composites lead to new or improved properties, how current biomedical research leverages these properties and the emerging directions in this growing field. Graphical abstract: Image, graphical abstract